2016
DOI: 10.1002/pc.23927
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chemical treatment on the structural and thermal, physical, and mechanical and morphological properties of roselle fiber‐reinforced vinyl ester composites

Abstract: Roselle fiber is a type of natural fiber that can potentially be used as a reinforcement material in polymer composites for different applications. This study investigated the chemical, physical, thermal, mechanical, and morphological characteristics of roselle fiberreinforced vinyl ester subjected to different fiber treatments. The roselle fiber was treated with alkalization and a silane coupling agent, and samples were prepared using the hand lay-up method. Treated roselle fiber significantly enhanced most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…Several studies have shown that the mechanical properties of a composite are strongly related to the matrix nature, fiber morphology, aspect ratio, fiber–matrix interface quality, as well as fiber type, concentration and orientation distribution . For example, the fibers in a thin plate tend to orient parallel to the flow direction near the walls due to shear stresses, while they tend to align perpendicular to the flow in the central zone .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the mechanical properties of a composite are strongly related to the matrix nature, fiber morphology, aspect ratio, fiber–matrix interface quality, as well as fiber type, concentration and orientation distribution . For example, the fibers in a thin plate tend to orient parallel to the flow direction near the walls due to shear stresses, while they tend to align perpendicular to the flow in the central zone .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the pine nut shell, an initial mass loss event at 30°C is observed, which is associated with the loss of absorbed water, typical of lignocellulosic materials [7] . In the range from 170°C to 295°C, there is another mass loss event related to the degradation of hemicellulose [5] . From 295°C to 330°C, cellulose degrades [27] , while lignin degrades between 330 and 500°C [28] .…”
Section: Tgamentioning
confidence: 99%
“…Composites made of biodegradable polymers and reinforced by natural fibers are an attractive option, since these fibers have some advantages when compared to synthetic ones, such as lower density, lower cost, and lower abrasivity during manufacturing. Besides, natural fibers are derived from renewable sources, are not toxic, and do not cause environmental impacts [1,[5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sugar palm tree, Arenga pinnata, comes from a forest plant that can be found abundantly in Southeast Asian countries such as Malaysia and Indonesia. It has been the topic of many research as a reinforcement in various polymer composites either in the form of short, long, random orientation and also in other types of fibre treatments [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Bachtiar et al [[39,40] treated sugar palm with various concentrations of NaOH and different soaking times.…”
Section: Formula Of Ifss τ = F/πdlmentioning
confidence: 99%